PARTICIPATION OF TLR4 IN ENGULFMENT OF ESCHERICHIA COLI BY HUMAN BLOOD NEUTROPHILS IN PRESENCE OF LIPOPOLYSACCHARIDES - S. V. Zubova; S. V. Grachev; I. R. Prokhorenko (Медицинская иммунология, 2014)
Abstract. TLR4 is a key player in signaling system of host cells. Possible role of TLR4 is actively discussed, e.g. its significance for phagocytosis. A capacity of neutrophils to engulf FITC-labeled E. coli bacteria upon activation with LPS of different origin was studied in presence of anti-TLR4 Mab’s (HTA125 clone). It was shown that, in whole blood, TLR4 does not play any essential role in engulfment of bacteria by the neutrophils. Phagocytic activity of neutrophils in blood increases increased after their priming with E. coli endotoxins. LPS from Rb. сapsulatus did not affect phagocytosis. In presence of endotoxins, the degree of TLR4 involvement in neutrophil phagocytosis depends on LPS structure.